MOTIVATION OF LATVIAN YOUNG ATHLETES TO BUILD A DUAL CAREER - Ābeļkalns, Ilvis; Kravalis, Ivars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The study explores factors that motivate high-performance athletes to manage their dual career while studying in secondary school. The dual career experience of Latvian youth is obtained. The paper analyses the results from young high-performance athletes’ questionnaire, focusing on the support young athletes receive and would need to receive in their education and sports training process. A survey, based on an individual approach, was carried out in training camps and schools; 125 high-performance athletes of the secondary school age completed the questionnaire (19 questionnaires were filled in electronically). The gained data were processed with the statistics methods using SPSS Statistics and Excel programmes. The young people in the age range from 15-19 years study in secondary school, vocational school or in Year 1 of a higher education institution; this is a young athletes’ transitional period from youth leagues to junior or adult sports leagues. In the education process, 77 young athletes were supported by their parents (M-3)(according to the average value of the 4-point Likert Scale), and 70 respondents indicated teachers’ support (M-3); while in sports the support was received from trainers (M-3,70) and friends (M-3,42). The study analysed the contributing factors that motivated young athletes to gain education and achieve sports mastery. Young athletes up to 19 years sought more for their friends’ approval. Student-athletes chose to study in schools that offered opportunities to combine studies with high-performance sports. However, young student-athletes lacked motivation for studies.